2022
DOI: 10.1021/acsagscitech.1c00259
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid-Functionalized CuO Nanoparticles Alter Biochemical Responses in Candyland Red Tomato (Solanum lycopersicum)

Abstract: Investigations on the effects of copper-based nanoparticles (NPs) on plant growth and fruit production have increased recently. However, limited studies have demonstrated the different impacts of pristine and surface-modified CuO NPs on tomato plants. In this study, Solanum lycopersicum Candyland Red variety tomatoes were exposed to either 50 or 500 mg/kg of synthesized pristine CuO (S.CuO), purchased pristine CuO (P.CuO), or functionalized CuO (F.CuO) NPs via soil application and grown to full maturity (120 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Moreover, after the second treatment and at harvest, there were no significant differences between the treatments and the controls. Similar findings were reported by Cantu et al, Adisa et al, and Barrios et al, where the nanotreatments had no effect on the chlorophyll content of Candyland red tomatoes (CuO and CuO-CA), Heirloom tomatoes (CeO 2 ), and Roma tomatoes (CeO 2 and CeO 2 -CA), at the end of the life cycle [11,12,16]. However, when the tomato was exposed to CuO and Al 2 O 3 NMs in the soil for 40 days, increased chlorophyll content was reported [42].…”
Section: Leaves Chlorophyll Productionsupporting
confidence: 88%
See 4 more Smart Citations
“…Moreover, after the second treatment and at harvest, there were no significant differences between the treatments and the controls. Similar findings were reported by Cantu et al, Adisa et al, and Barrios et al, where the nanotreatments had no effect on the chlorophyll content of Candyland red tomatoes (CuO and CuO-CA), Heirloom tomatoes (CeO 2 ), and Roma tomatoes (CeO 2 and CeO 2 -CA), at the end of the life cycle [11,12,16]. However, when the tomato was exposed to CuO and Al 2 O 3 NMs in the soil for 40 days, increased chlorophyll content was reported [42].…”
Section: Leaves Chlorophyll Productionsupporting
confidence: 88%
“…Several studies involving the exposure of metal oxide nanomaterials on tomato plants have shown similar nonsignificant effects. Cantu et al found that there was no net effect on the agronomical parameters when tomato plants were exposed to CuO NPs and grown to full maturity (120 days) [ 16 ]. Adisa et al and Barrios et al also showed that soil or foliar application of CeO 2 NPs on tomato did not alter plant growth at concentrations below 250 mg/kg and 250 mg/L when grown for 126 and 210 days, respectively [ 11 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations